Pembelajaran Fisika Berbasis Masalah di Era Pandemi untuk Mengembangkan Keterampilan Berpikir Kritis dan Kreatif - Septeanawati, Melisa; Yulianti, Dwi (UPEJ Unnes Physics Education Journal, 2021)
Distance learning or online learning in Indonesia has been implemented since April 2020 to break the chain of the spread of Covid-19. Online learning activities involve adequate network of connections and support learning devices. Thinking skills that must be prossesed by students in improving the quality of education graduates two of which are critical thinking skiils and creative thinking skills. The purpose of the study was determine the development of student critical and creative thinking skills in problem based physics learning. Thinking skills are developed to develop three indicators, namely analyzing, synthesizing, and researching. The creative thinking skills developed consist of three indicators, namely realizing, elaborating, and formulating. This research method is quasi-experimental using one group pretest-posttest design. The sample in this study was class XI MIPA 1 and XI MIPA 2. This research was carried out for two meetings at SMA Negeri 2 Kendal using a problem based learning model. Based on the results of problem-basel physics learning, it shows that it is able to develop critical and creative thingking skills with moderate criteria.